UPAYA GURU DALAM PEMBENTUKAN MORAL SISWA MA BAHRUL ULUM LAMONGAN MELALUI MUATAN PELAJARAN BACA TULIS AL-QUR’AN - M Zainuddin Alanshari; Siti Khusnul Khotimah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2022)
The title of this research is the teacher's efforts in forming students' morale through the content of reading and writing Al-Qur’an lessons at MA Bahrul Ulum Lamongan. Using the type of qualitative research and case study approach. The purpose of this study was to find out how the teacher's efforts in producing moral formation through the content of reading and writing Al-Qur’an lessons at MA Bahrul Ulum Lamongan in the 2021/2022 academic year. From the results of this study, the first is the process of teaching and learning to read and write Al-Qur’an at MA Bahrul Ulum in the form of formal learning and tahfidz Al-Qur’an. Formal learning is presented in the form of classroom learning using the basics of tajwid written by KH. Muhammad Basori Alwi Murtadho Singosari Malang with the lecture method and the preparation of tajwid nadzom creatively. As for the tahfidz Al-Qur’an program, it is actualized using the deposit method (talaqqi) and murajaah. Second, the moral formation of students through the content of reading and writing Al-Qur’an cannot be separated from the efforts of teachers who actualize the values of teacher competence and carry out their roles as educators, role models, facilitators, motivators and student evaluators seriously, so that it can result in the formation of habits of actualizing positive morals in students' personalities. As for the factors that hinder the progress of the teacher's efforts in shaping the morale of MA Bahrul Ulum Lamongan students, one of which is more dominant is the influence of the external environment of each student.